Influences of main machining process parameters and tool wear on the machining damage generated during edge milling CFRP composites / Nguyen Thi-Hue and Nguyen Dinh-Ngoc - Nguyen, Thi-Hue; Nguyen, Dinh-Ngoc (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
Machining Carbon Fibre Reinforced Plastics (CFRPs) composites are typically accompanied by the appearance of machining damage which strongly impacts the structural integrity of composite parts during their service lives. Studying the correlation between machining damage and its affected factors has still been an open issue. Hence, it is necessary to do more research. This study focuses on investigating the influences of main process parameters and tool wear phenomenon in terms of machining length on the machining quality which was characterized by the surface roughness criterion, the ten-point max, Rz. A full factorial design of experiments was conducted including three levels of feed speed and two degrees of spindle speed. The results revealed that machining damage was mainly influenced by process parameters at a small machining distance, whereas at a longer machining distance, tool wear had a dominant effect on the machining quality than machining parameters. These findings could provide guidelines for selecting suitable machining parameters to enhance the machining quality of CFRP.